Grids, Clouds and Virtualization - Cafaro, Massimo; Aloisio, Giovanni; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Research into grid computing has been driven by the need to solve large-scale, increasingly complex problems for scientific applications. Yet the applications of grid computing for business and casual users did not begin to emerge until the development of the concept of cloud computing, fueled by advances in virtualization techniques, coupled with the increased availability of ever-greater Internet bandwidth. The appeal of this new paradigm is mainly based on its simplicity, and the affordable price for seamless access to both computational and storage resources. This timely text/reference introduces the fundamental principles and techniques underlying grids, clouds and virtualization technologies, as well as reviewing the latest research and expected future developments in the field. Readers are guided through the key topics by internationally recognized experts, enabling them to develop their understanding of an area likely to play an ever more significant role in coming years. Topics and features: Presents contributions from an international selection of experts in the field Provides a thorough introduction and overview of existing technologies in grids, clouds and virtualization, including a brief history of the field Examines the basic requirements for performance isolation of virtual machines on multi-core servers, analyzing a selection of system virtualization technologies Examines both business and scientific applications of grids and clouds, including their use in the life sciences and for high-performance computing Explores cloud building technologies, architectures for enhancing grid infrastructures with cloud computing, and cloud performance Discusses energy aware grids and clouds, workflows on grids and clouds, and cloud and grid programming models Presents case-studies and novel results related to interoperability across grids and clouds This useful text will enable interested readers to familiarize themselves with the key topics of grids, clouds and virtualization, and to contribute to new advances in the field. Researchers, undergraduate and graduate students, system designers and programmers, and IT policy makers will all benefit from the material covered. Dr. Massimo Cafaro is Assistant Professor at the Department of Engineering for Innovation at the University of Salento, Lecce, Italy. Dr. Giovanni Aloisio is Full Professor of Information Processing Systems at the Department of Engineering for Innovation at the University of Salento, Lecce, Italy.
Grids, Clouds, and Virtualization -- Quality of Service for I/O Workloads in Multicore Virtualized Servers -- Architectures for Enhancing Grid Infrastructures with Cloud Computing -- Scientific Workflows in the Cloud -- Auspice: Automatic Service Planning in Cloud/Grid Environments -- Parameter Sweep Job Submission to Clouds -- Energy Aware Clouds -- Jungle Computing: Distributed Supercomputing beyond Clusters, Grids, and Clouds -- Application-Level Interoperability Across Grids and Clouds.
Keywords: Computer science; Software engineering; Computer system performance; Information Systems; Computer Science; Special Purpose and Application-Based Systems; System Performance and Evaluation; Software Engineering; Management of Computing and Information Systems